The Nationalist Instrumentalization of Religion in Secularizing Societies: Fighting against the Private Theological-Philosophical Luther Academy in Early 1930s Estonia - Tark, Triin (Religion and society in Central and Eastern Europe, 2024)
This article analyses a controversy in early 1930s Estonia concerning the German language Private Theological-Philosophical Luther Academy. The article discusses this case as an example of the nationalist instrumentalization of religion in secularizing societies, which interwar Estonia was turning into. An analysis of the press coverage concerning the Luther Academy shows that the case received a disproportionate amount of attention considering the marginality of this small educational institution, yet the reactions were ambiguous. On the one hand, the academy was presented as a nationalist project by Germans to restore their power and as an existential threat to the survival of Estonians as an ethnic group, inasmuch as it allegedly facilitated the Germanization of Estonians. On the other hand, it was claimed that the whole controversy was artificially inflated and the academy was not posing a particular threat to Estonians. This article argues that the quarrel stemmed from the instrumentalization of the case by some Estonian nationalist circles, whereas extensive public attention was ensured by associating the academy with the issue of Germanization which had been a significant subject of press interest for many years.